Analysis of Development Stages and Digital Start-Up Success Factors - Ratri Isharyadi; Riska Novia Sari; Purwantoro Purwantoro (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of start-ups in Indonesia is very fast. Every year new startup appear with a pretty fantastic number. This year, Indonesia occupies the fifth position in the country with the highest number of start-ups. Along with the many new start-ups that appear, there are also many start-ups that fail in the middle of the road. This failure can be caused by many factors. This study aims to examine the stages of development and key factors for the success of digital start-ups. This type of research is descriptive qualitative research. The research sample consists of 15 CEOs or founders of digital start-up registered on the https://1000start-updigital.id/ website with a random method. The results of the analysis show that the start-up development stage consists of 7 stages including: ideation, making a business plan, building a team, making MVP, testing MVP to validate solution ideas, refinement, launching. Furthermore, to overcome start-up failures, there are key success factors including teamwork, capital, role models, and innovation. The findings in this study indicate that the team is the main factor for the success of a start-up.